2019
DOI: 10.3389/fpsyg.2019.01974
|View full text |Cite
|
Sign up to set email alerts
|

May Subjective Language Complaints Predict Future Language Decline in Community-Dwelling Subjects?

Abstract: Subjective cognitive complaints are rather prevalent in the elderly population and are associated with an increased risk of cognitive impairment and dementia. However, the predictive role of specific types of cognitive complaints has been less systematically assessed. The aim of the present study is to examine the predictive value of language complaints for cognitive and language decline in a cohort of community-dwelling healthy older adults, followed longitudinally over a 5-year period. A total of 402 subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…All, except one (Maruta et al, 2019), of the 11 studies reporting odds ratio for incident MCI also reported increased risk (odds ratio>1) of incident MCI for participants with SCD, as shown in Figure 5. Odds ratio estimates ranged considerably, from 0.95 to 17.71, and overall people with SCD demonstrated almost twice the odds of developing incident MCI compared to those without SCD (OR = 1.83, 95% CI: 1.56-2.16).…”
Section: Results Of Individual Studies and Synthesis Of Resultsmentioning
confidence: 90%
See 3 more Smart Citations
“…All, except one (Maruta et al, 2019), of the 11 studies reporting odds ratio for incident MCI also reported increased risk (odds ratio>1) of incident MCI for participants with SCD, as shown in Figure 5. Odds ratio estimates ranged considerably, from 0.95 to 17.71, and overall people with SCD demonstrated almost twice the odds of developing incident MCI compared to those without SCD (OR = 1.83, 95% CI: 1.56-2.16).…”
Section: Results Of Individual Studies and Synthesis Of Resultsmentioning
confidence: 90%
“…Seven authors responded and provided the requested data (Ebenau et al, 2020;Jorm et al, 1997;Kryscio et al, 2014;Maruta & Martins, 2019;St John & Montgomery, 2002;van Harten et al, 2018), including Tomata et al (2016) who provided a copy of a then in-press article (Tomata et al, 2017) which provided relevant data, and was included in the synthesis.…”
Section: Data Extractionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most studies on the objectification of cognitive differences between individuals with SCD and healthy controls (HCs) have focused on the predictive value of cognition questionnaires. For example, Maruta and Martins showed that individuals with language complaints performed significantly worse on semantic fluency tasks than the HCs after five years, even though their rate of decline was similar overall and unrelated to subsequent cognitive decline [ 18 ]. Based on the findings of a six-year longitudinal study, Brailean et al argued that a decrease in subjective memory performance that cannot be explained by depressive symptoms may be detected by self-reported memory complaints [ 19 ].…”
Section: Introductionmentioning
confidence: 99%